The Implementation of the Demonstration and Drill Methods in Teaching the Hijaiyah Alphabet as the Foundation of Early Childhood Quran Education - Adinda Zahrah; Amirudin; Ferianto (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2026)
This study aims to analyze the implementation of demonstration and drill methods in learning hijaiyah letters at a nonformal calistung tutoring institution. This study used a qualitative descriptive approach with field research methods. The research subjects consisted of one teacher and three students aged 5–7 years. Data were collected through observation, interviews, and documentation, while data analysis used the Miles and Huberman model with source triangulation to test data validity. The results showed that the demonstration method was implemented through direct examples in introducing the forms, sounds, and writing of hijaiyah letters, while the drill method was applied through repetitive reading exercises, individual Iqro reading activities, and repeated hijaiyah writing practices. The use of learning media such as whiteboards, Iqro books, hijaiyah exercise books, and colorful origami paper helped increase students’ attention and involvement during the learning process. The implementation of both methods helped students gradually recognize, read, and write hijaiyah letters according to their respective abilities.